Disruptive Crises, Institutional Pressures and Climate Action: Understanding Business Investment Decisions in Climate Technologies - García-Sánchez, Isabel-María; Aibar-Guzmán, Beatriz; Aibar-Guzmán, Cristina; David, Fátima (JOINETECH, 2026)
Climate technologies aim to reduce CO2 emissions in order to mitigate the effects of global warming. In this paper, we analyse whether the disruptive events that we have been experiencing since 2020 (specifically, the COVID-19 pandemic and the war in Ukraine) act as drivers of firms' investment in climate technologies, and whether the institutional environment of the European Union also does so. For a sample of 5,376 firms for the period 2016-2022, we find that firms' investment in climate technologies is higher in disruptive periods. Moreover, we observe that this effect is smaller than the driving effect of the EU institutional environment on firms' engagement in the fight against climate change and investment in climate technologies.
Keywords: climate change; climate technology; disruptive events